Impact of artificial intelligence on supply chain management: Requirements for human-artificial intelligence collaboration - Mahmood, Abdul Hayee (İstanbul Sabahattin Zaim Üniversitesi, 2022)
This is an exploratory study and analyze the impact of artificial intelligence (AI) on supply chain management (SCM) and the requirements for Human-AI collaboration. New trends of AI technologies in the supply chain brought new challenges. So, there will be an analysis of sub-fields of AI which are more suitable to SCM. Human-AI collaboration requires new roles, high educated and skilled workers. With growing AI technologies, there are limited numbers of high-skilled employees in most regions of the world. AI is increasing the competition among the companies, increasing the need for new job qualifications. Therefore, workers must improve and develop both technical and non-technical capabilities. Innovative humans and AI technology should work together as partners rather than competitors to strengthen one another. This human-AI collaboration establishes super minds that are cleverer than any person or group in our world. This study employs quantitative and qualitative analyses to demonstrate the importance of education/training and skills requirements in human AI collaboration. The study result indicates that firms generally use artificial intelligence in their SCM. The research determined that the companies should have lifelong training programs for employees to get a competitive advantage. There should be mutual readiness of employees and employers to accept the change.

Bu bir keşif çalışmasıdır ve yapay zekanın tedarik zinciri yönetimi üzerindeki etkisini ve İnsan-yapay zekâ iş birliği gereksinimlerini araştırmaktadır. Yapay zekâ teknolojilerinin tedarik zincirindeki yeni trendleri yeni zorlukları da beraberinde getirdi. Böylece, tedarik zinciri yönetimine daha uygun olan yapay zekânın alt alanlarının bir analizi yapılacaktır. İnsan- yapay zekâ iş birliği, yeni roller, yüksek eğitimli ve nitelikli işçiler gerektirir. Artan yapay zekâ teknolojileri ile dünyanın çoğu bölgesinde sınırlı sayıda yüksek nitelikli çalışan var. Bu nedenle, işçiler hem teknik hem de teknik olmayan yetenekleri geliştirmelidir. Yenilikçi insanlar ve yapay zekâ teknolojisi, birbirlerini güçlendirmek için rakip değil ortak olarak çalışmalıdır. Bu insan-yapay zekâ iş birliği, dünyamızdaki herhangi bir kişi veya gruptan daha zeki süper zihinler oluşturur. Bu çalışma, insan ve yapay zekâ iş birliğinde eğitim/öğretimin ve beceri gereksinimlerinin önemini göstermek için nicel ve nitel analizler kullanmaktadır. Araştırma sonucu, firmaların tedarik zinciri Yönetim'lerinde genellikle yapay zekâ kullandıklarını gösteriyor ve rekabet avantajı elde etmeleri için şirketlerin yaşam boyu eğitim programlarına sahip olmaları gerektiğini belirledi. Çalışanların ve işverenlerin değişikliği kabul etmeye karşılıklı hazırlığı olmalıdır.
Yapay zekanın tedarik zinciri yönetimi üzerindeki etkisi: İnsan- yapay zekâ işbirliği için gereklilikler
Keywords: Artificial intelligence; Supply chain; Human-AI collaboration; Technological trends; Competition; Job qualifications; Tedarik zinciri yönetimi; Yapay zekâ; Teknoloji; Rekabet avantajı